Numerical Investigation of the Effects of the Beam Scanning Pattern and Overlap on the Temperature Distribution during the Laser Dopant Activation Anneal Process - Donghyeok Choi (MDPI AG, 2021)
Laser thermal annealing (LTA) has played an important role in the fabrication of scaled semiconductor devices by reducing the heat budget of the dopant activation process. During the laser annealing of entire wafer areas, the beam scanning pattern and overlap ratio have significant effects on uniform heating during the process. In this study, a numerical simulation of the LTA process was carried out using a three-dimensional transient heat transfer model. The temperature distribution produced by different laser scan paths and beam overlap ratios was analyzed. Additionally, the behavior of the dopant (phosphorus) diffusion induced under the multipath and beam overlapping conditions was numerically investigated. According to the simulation result, a zig-zag pattern generated hot spots around the corner areas of the beam path due to the greater heat accumulation per unit area; however, a bidirectional pattern induced cold spots due to the absence of laser heating around the corner areas. It was also found that the maximum temperature reachable in the beam overlapped region was much lower than that obtained along the beam scanning path, and the most uniform heating could be obtained when the zig-zag pattern and a 50% overlap ratio were used. According to the dopant diffusion and concentration distribution predicted for the case of the zig-zag pattern and 50% overlap ratio, the difference in the dopant diffusion length was approximately thirty times within the scanned area.